المركز القانوني لرئيس الحوومة والوزير الاولفي التعديل الدستوري 2020 - عباد, محمد أمير (جامعة الوادي.University eloued, 2021)
إن منصب الوزير الأول أو رئيس الحكومة حسب ما جاء في التعديل الدستوري 2020 يعتبر تعديلا بارزا لمكانة هذا المنصب داخل السلطة التنفيذية الى جانب رئيس الجمهورية، وفي ظرف استثنائي وأمام تحديات سياسية اقتصادية كبيرة تعيشها الجزائر توحي بأهمية ومركز هذا المنصب في إعادة بناء جزائر جديدة على جميع الأصعدة السياسية والاقتصادية، لهذا خصه المؤسس الدستوري بمكانة خاصة تتجسد من خلال استعمال تسمية الوزير الأول ورئيس حكومة في نفس الدستور التي تعتبر سابقة سواء في الدساتير الجزائرية أو حتى النظم السياسية المقارنة والتي تقابلها الحالة التي يقود فيها الحكومة وزير أول الذي يكون منفذ لبرنامج الرئيس بعد المصادقة عليه والحالة التي يقود فيها الحكومة رئيس حكومة معين من الأغلبية البرلمانية ومنفذا لبرنامجها، كما تتجسد المكانة الدستورية من خلال الصلاحيات الممنوحة لهذا المنصب يمارسها بمفرده كصلاحيات تنفيذية وإدارية الى جانب صلاحيات استشارية مع رئيس الجمهورية في ظروف عادية وأخرى غير عادية، كما أن هذThe position of Prime Minister or Head of Government, according to what was stated in the constitutional amendment 2020, is considered a prominent amendment to the position of this position within the executive authority alongside the President of the Republic, and in an exceptional circumstance and in the face of great political and economic challenges that Algeria is experiencing, suggesting the importance and center of this position in rebuilding a new Algeria on all The political and economic levels, that is why the constitutional founder assigned him a special status embodied through the use of the designation of the Prime Minister and Head of Government in the same constitution, which is considered a precedent, whether in the Algerian constitutions or even comparative political systems, which corresponds to the situation in which the government is led by a Prime Minister who is executing the President’s program after ratification And the situation in which the government is led by a certain prime minister from the parliamentary majority and implements its program, and the constitutional status is embodied through the powers granted to this position, which he exercises alone as executive and administrative powers, in addition to advisory powers with the President of the Republic in normal and unusual circumstances, and this position has Powers that affect Parliament, such as summoning the latter to extraordinary sessions, as well as summoning the committee with equal members.ا المنصب له صلاحيات يؤثر بها على البرلمان كاستدعاء هذا الأخير لدورات غير عادية و كذلك استدعاء اللجنة متساوية الأعضاء.
قانون اداري
Keywords: رئيس الحكومة، الوزير الأول، السلطة التنفيذية، التعديل الدستوري 2020، النظام الدستوري الجزائري; Head of Government, Prime Minister, Executive Branch, Constitutional Amendment 2020, Algerian constitutional system.